A population-based study of 15,000 people on Knowledge and awareness of lung cancer symptoms and risk factors in Saudi Arabia - AlRabeeah, Saad M.; Alzahrani, Eidan M.; Aldhahir, Abdulelah M.; Siraj, Rayan A.; Alqarni, Abdullah A.; AlDraiwiesh, Ibrahim A.; Alqahtani, Abdullah S.; Almqati, Badr S.; Alharbi, Turki G.; Almuntashiri, Abdulraheem A.; Alghamdi, Saeed M.; Aljohani, Fahad E.; et al. (Frontiers in Oncology, 2024)
Background ‎ Lung cancer is currently the most fatal form of cancer worldwide, ranking as the fourth most ‎prevalent type in Saudi Arabia, particularly among males. This trend is expected to increase with ‎growing population, lifestyle changes, and aging population. Understanding the awareness of the ‎Saudi population regarding the risk factors and symptoms of lung cancer is necessary to attenuate ‎the predicted increase in cases.‎ Method ‎ A cross-sectional, population-based survey was performed using a previously validated ‎questionnaire (Lung CAM). Multiple linear regression analysis was used to assess variables ‎associated with deficiency in knowledge and awareness of risk factors and symptoms of lung ‎cancer. ‎ Results ‎ Majority of the 15,099 respondents were male (65%), aged between 18 and 30 years (53%), ‎‎50% of which were educated up to a bachelor’s degree level. Overall awareness of lung ‎cancer signs and symptoms was 53%, with painful cough and coughing up blood being the ‎best-known symptoms. Conversely, persistent shoulder pain (44%) and clubbing fingers ‎‎(47%) were the least known lung cancer symptoms. Also, 60% of the respondents showed ‎low confidence in identifying the signs and symptoms of lung cancer. The overall awareness ‎of the risk factors for lung cancer development was 74%, with first-hand (74%) and second-‎hand (68%) smoking being the most known risk factors. However, only ≤ 62% know the other ‎non-smoking risk factors. Awareness of the risk factors and symptoms of lung cancer ‎depended on age, gender, education, marital and employment status (p < 0.001).‎ Conclusion ‎ Public awareness of the risk factors and symptoms of lung cancer in Saudi Arabia is ‎inadequate and heavily dependent on education and socio-economic status. Awareness can ‎be improved through campaigns to raise awareness about other lesser-known lung cancer ‎risk factors and symptoms. ‎